Development of methodologies for the complete utilization ofo poultry abattoir waste - PARVATHY MENON; Rahul S. Warrier; Er. Vishnu B (Guide) (Tavanur 2013 Department of Land and Water Resources & Conservation Eng i- neering)
Development of methodologies for the complete utilization ofo poultry abattoir waste
Development of methodologies for the complete utilization ofo poultry abattoir waste